MicroRNAs expression in semen and testis of azoospermic men. (6th February 2023) - Wainstein, Amit; Hassan, Sarah; Barda, Shimi; Lehavi, Ofer; Azem, Foad; Ben‐Dov, Iddo Z.; Hauser, Ron; Kleiman, Sandra E.
Abstract: Background: MicroRNAs are involved in the regulation of spermatogenesis, are detected in semen and may be useful as molecular markers for predicting residual complete spermatogenesis in azoospermic men. Objectives: To study the biomarker potential of microRNAs that are detected in semen and testicular tissue. Materials and methods: MicroRNA profiles were analyzed in semen fractions of normozoospermic ( n = 3) and azoospermic ( n = 6) men by small RNA deep sequencing. Specific microRNAs were further analyzed by reverse transcription and quantitative polymerase chain reaction in eight testicular samples and 46 semen supernatants. The semen supernatant samples included 18 normozoospermic and 28 azoospermic men with various pathologies. Results: The sequenced microRNA profiles of semen supernatant fraction samples were distinct from the other fractions. Significant expression differences were observed between the semen supernatant of normozoospermic and azoospermic men. Further analysis by reverse transcription and quantitative polymerase chain reaction revealed that expression of miR‐202‐3p was considerably reduced (undetectable in most samples) in the azoospermic semen supernatants. The expression of miR‐202‐3p was significantly lower in the azoospermic specimens than in the normozoospermic specimens and a trend was observed for miR‐629‐5p ( p = 0.03 and 0.06, respectively). Differences in expression levels in the semen supernatant were observed among the various pathologies but not to a level of significance, possibly because of the small subgroups. miRNA‐370‐3p was significantly higher in semen supernatant samples from azoospermic men without sperm cells in testis ( p = 0.05). In testes, the three microRNAs were expressed at higher levels in the obstructive and spermatocyte maturation arrest pathologies than in mixed atrophy and Sertoli cell only. miR‐202‐3p was detected in all testicular samples. Conclusions: MicroRNA expression profiles in semen were distinguishable between azoospermic and normozoospermic men. The microRNA profile also diverged among azoospermic men subdivided according to their testicular pathologies. The levels of specific microRNAs in testis and in the semen supernatant were not directly correlated.